2019
DOI: 10.1103/physrevb.100.020401
|View full text |Cite
|
Sign up to set email alerts
|

Towards experimental observation of parametrically squeezed states of microwave magnons in yttrium iron garnet films

Abstract: We demonstrate theoretically, and confirm experimentally, that nonlinear spin waves excited in thin yttrium iron garnet films are good candidates for squeezing vacuum quantum noise. The experimental demonstration is in the form of a measurement of spin-wave induced modulation instability (IMI) conducted in the classical regime. The experiment evidences strong phase locking of an idler wave parametrically generated in the film with a deterministic small-signal wave launched into the film from an external source… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…This can open a new avenue for coherent nonlinear nano-magnonics. Our study can be used for several device architectures, namely, frequency mixers [43], squeezed states [44], signal and data processing units [29,[45][46][47][48], and quantum computing concepts [23], and further open doors to engineered dissipation of magnons in nano-devices.…”
mentioning
confidence: 99%
“…This can open a new avenue for coherent nonlinear nano-magnonics. Our study can be used for several device architectures, namely, frequency mixers [43], squeezed states [44], signal and data processing units [29,[45][46][47][48], and quantum computing concepts [23], and further open doors to engineered dissipation of magnons in nano-devices.…”
mentioning
confidence: 99%
“…The great potential of YIG as the key magnetic material for quantum magnonics is yet to be realized. For instance, there are only a few experiments done at room temperature to demonstrate the possibility of magnon state squeezing [452], magnon BEC supercurrents, and Bogoliubov waves [429], [430], [453]. The only attempt to study magnon BEC at cryogenic temperatures was reported in [454] but a thorough investigation in the quantum limit is still needed.…”
Section: B Yig-based Quantum Magnonicsmentioning
confidence: 99%
“…The magnetoelastic interaction helps to generate [522], transfer, and manipulate magnon-magnon entanglement via phonons. Analogous to atoms in Bose condensate and photonic solitons, magnons can be entangled in real rather than reciprocal-space in interacting magnon condensates or soliton wave functions whose fluctuations are squeezed by four magnon interactions [452].…”
Section: How To Distill Entanglement In Quantum Magnonicsmentioning
confidence: 99%
“…Parallel parametric pumping has proven to be a promising way to generate and amplify propagating SWs . Parallel pumping can be realized when a pumping radio frequency microwave (magnetic) field is applied parallel to the static magnetization of a uniformly magnetized film.…”
mentioning
confidence: 99%